Postgraduate teacher education in post-Soviet countries - Saliyenko, E. (Problems of Engineer-Pedagogical Education, 2020)
The retrospective analysis of the development of postgraduate education in the post-Soviet space is conducted in the work. The analytical and descriptive method of studying and generalizing the theory and experience of teaching in higher education establishments, critical analysis of scientific literature on pedagogy and teaching methods on the topic of research are used for the analysis. The retrospective analysis of the development of postgraduate education in the post-Soviet space, in such post-Soviet countries as Ukraine, Republic of Moldova, Republic of Belarus, Republic of Kazakhstan and Latvia, is carried out in the work. Among the post-Soviet countries, the experience of the countries of the South Caucasus region, including Georgia, is noteworthy in this area. One of the modern innovations of the Georgian education system has been the mandatory recertification of teachers (every seven years). Lifelong education is positioned as an effective tool for the formation of highly skilled personnel who, in times of dynamic changes, will meet the demands of society and the labor market. At the present stage of the modernization of pedagogical education, the countries of this region pay particular attention to teacher education throughout their lives. This is evidenced not only by recertification, but also by attending seminars and conferences by teachers, distance education at pedagogical universities, shortterm advanced training and retraining courses at institutions of retraining and postgraduate education, research work, postgraduate studies, and professional associations for pedagogues. The periods of formation and development of the system of professional development of pedagogical staff of education institutions in Ukraine from 1900 to the present are also determined. The paper mainly focuses on to the historical period (1917-1941), further reveals the times of stagnation and Perestroika (1945- 1990), and the analysis of postgraduate pedagogical education in the first years of the independence of Ukraine. In the current conditions of globalization and integration of society, a significant contribution has been made to the normative and legal support of the postgraduate education system. We refer to the following legal framework of the system of postgraduate pedagogical education: Laws of Ukraine "On Education", "On Higher Education", State National Program "Education" ("Ukraine of the 21st Century"),"National Doctrine of Educational Development", "Concept State Program for the Development of Education for 2006-2020” and other legal documents. The forms, content, duration and frequency of advanced training courses for managerial and teaching staff in each period are revealed. The peculiarities of the organization, models, forms, directions, duration and content of postgraduate teacher training programs in post-Soviet countries are characterized. The content of the postgraduate teacher education is realized through the development of the teacher's independent and research work; active and interactive teaching methods; advanced training courses, methodological seminars, conferences, group and individual forms of work.